Assessment of the Gambian Police Force on Crime Prevention and Control - Gibba, Kebba; Sawaneh, Banna; Fanneh, Momodou Mustapha; Obah-Akpowoghaha, Nelson Goldpin (Journal of Contemporary International Relations and Diplomacy, 2023)
The study assessed the Gambia Police Force (GPF) on Crime Prevention and Control in the Greater Banjul Area of The Gambia from 2017 to 2019. The study used both primary and secondary data. Primary data were collected using questionnaires and interview guides. The targeted population for this study was serving members of The Gambia Police Force (GPF), and 254 members were sampled out of 700 populations using the Taro Yamane formula. The distribution of the sample size was based on convenient sampling in terms of accessing major police stations and police posts. In the course of the fieldwork, 254 copies of the questionnaire were administered with the aim of retrieving the required number meant for the study. The study used descriptive and inferential statistical tools to analyse the data. Three interviews were conducted with officials from GAF, NAATIP, and WANEP who are knowledgeable on the subject of investigation. The selection and distribution of the numbers of respondents were purposively interviewed. The findings of the study revealed that the GPF used outdated gadgets and human intelligence as methods and approaches in responding to crime prevention and control in the country. The study also revealed that GPF faced certain operational limitations in using modern security tools. This was due to inadequate exposure in terms of training and the challenge of the apolitical among the ranks and files of the GPF. The study identified copious challenges facing GPF which is a general issue in most African countries based on the extant literature. The challenge of funding; corruption; political interference; indiscipline; non-compliance and reporting of some citizens and so on, have constituted some level of hindrances to the GPF on crime prevention and control in The Gambia. This paper evaluates the effectiveness of the methods and approaches used by the GPF on crime prevention and control; and assess the challenges facing the GPF on crime prevention and control in the Gambia (GBA).